Short-term return-based contrarian strategies in US future markets : 1987-2002 - Koh, Loh Pin (2008)
In this paper, we document return reversals and investigate short-term contrarian profitability in the US futures markets, on 4 segments consisting of 29 futures contracts. Our methodology closely follows the spirit behind the Lo and MacKinlay (1990) methodology that are used for contrarian strategies in equity market.